ANALISIS SPASIAL FAKTOR LINGKUNGAN LEPTOSPIROSIS DI KECAMATAN BONANG KABUPATEN DEMAK TAHUN 2018 - Widya Hary Cahyati; Lia Diah Kumalasari (Dian Nuswantoro Semarang, 2020)
The number of leptospirosis cases in Demak district had a significant increase in 2018 which reached 92 cases with IR = 7.91% and the death of 24 people with CFR = 28.09%. Bonang Subdistrict is a sub-district with a case of the highest leptospirosis in Demak district. The aim of this research is to spatial analyze the environmental factors of leptospirosis in Kecamatan Bonang include flood/rob history, garbage storage, river, paddy field, fishpond, and population density. This type of research is quantitative descriptive with cross sectional design. The samples in this study numbered 24 people. This research was conducted in June 2019 in Bonang Sub-district of Demak Regency. The results showed that the pattern of the leptospirosis case in sub-district Bonang was scattered uneven. In this study can be concluded that the most influential risk factors in the distribution of leptospirosis cases in Bonang sub-district is a bad condition of individual garbage storage and the existence of paddy fields and rivers that are close to the house cases.Keywords: Spatial Analysis, GIS, Leptospirosis